2017
DOI: 10.1016/j.aju.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coexisting sperm DNA fragmentation and seminal oxidative stress on the outcome of varicocelectomy in infertile patients: A prospective controlled study

Abstract: ObjectivesTo study the relationship between sperm DNA fragmentation (SDF) and reactive oxygen species (ROS) levels in infertile patients with varicocele, and to examine the beneficial effect of varicocelectomy and elucidate predictors of improvement after repair.Patients, subjects and methodsWe prospectively studied 60 patients with varicocele and abnormal semen variables who attended the outpatient clinic complaining of infertility for ≥12 months. In all, 25 patients (41.7%) had bilateral varicoceles and 35 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 54 publications
5
37
0
Order By: Relevance
“…Furthermore, the levels of sperm DNA fragmentation were designated based on the following criteria: low SDF level (0-15% sperm cells with fragmented DNA, high fertility potential), moderate SDF level (16-30%, moderate fertility potential) and high SDF level (> 30%, low fertility potential) [7,[10][11][12]. Healthy volunteers and infertile men differed significantly (p < 0.0001) at low levels (57.90% vs 17.03% subjects, respectively) and high levels (5.26% vs 35.17% subjects, respectively) of SDF (Tab.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the levels of sperm DNA fragmentation were designated based on the following criteria: low SDF level (0-15% sperm cells with fragmented DNA, high fertility potential), moderate SDF level (16-30%, moderate fertility potential) and high SDF level (> 30%, low fertility potential) [7,[10][11][12]. Healthy volunteers and infertile men differed significantly (p < 0.0001) at low levels (57.90% vs 17.03% subjects, respectively) and high levels (5.26% vs 35.17% subjects, respectively) of SDF (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Bungum et al [18] showed that in the range of 0-20% sperm DNA fragmentation, the chance of a spontaneous pregnancy was constant, while DNA fragmentation index (DFI) levels > 30-40% resulted in reduced chances close to zero. However, these 2 categories can reasonably be extended to 3, as proposed by Leach et al [7], Abdelbaki et al [10] and Al Omrani et al [12]. In this division, a threshold of 0-15% is considered a high fertility potential, while 16-30% and > 30% are considered moderate and low fertility potentials, respectively.…”
Section: Sdf Measured By the Halosperm Test Reflects Male Fertility Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation between varicocoele (uni‐ or bilateral) and OAT is controversial, due to its presence both in adult men with normal semen analysis and men with OAT (World Health Organization, ). Recent meta‐analyses show semen quality improvement following palpable varicocoele repair (Marmar et al ., ), possibly with a higher conception rate after surgery vs. no‐surgery (Agarwal et al ., ; Marmar et al ., ; Abdel‐Meguid et al ., ; Baazeem et al ., ; Kroese et al ., ), and sperm DNA damage decrease (Abdelbaki et al ., ). In addition, varicocelectomy may increase total testosterone level in hypogonadal men with subfertility (Chen et al ., ).…”
Section: Surgical Treatment Of Oatmentioning
confidence: 97%
“…The surgical treatment of varicocele has been demonstrated to be an effective method to remove the alterations caused by the affected veins, as blocking blood reflux prevents temperature increases. The effects observed after the recovery from surgery include a decrease in reactive oxygen species and an increase in total antioxidant capacity, which comes from augmenting the levels of antioxidant enzymes and molecules [27,103,104]. As a consequence, DNA damage is reduced after varicocelectomy [105].…”
Section: Varicocelectomymentioning
confidence: 99%